2018
DOI: 10.3390/toxins10110463
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Boar Spermatozoa as a Biosensor for the Detection of Sublethal and Lethal Toxicity

Abstract: A novel, objective, and rapid computed motility inhibition (CMI) assay was developed to identify and assess sublethal injury in toxin-exposed boar spermatozoa and compared with a subjective visual motility inhibition (VMI) assay. The CMI values were calculated from digital micrographic videos using a custom MATLAB® script by contrasting the motility index values of each experiment with those of the background and control experiments. Following a comparison of the CMI and VMI assays results, it was determined t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(45 citation statements)
references
References 26 publications
0
45
0
Order By: Relevance
“…The two screening assays detected sublethal toxins disturbing cellular energy metabolism (BSMI) as well as toxins affecting cellular proliferation (ICP) [18]. Screening of the biomass suspensions from individual colonies separated the ophiobolin-producing colonies by exhibiting a low toxic response (EC 50 < 2 µg mL −1 ) in both toxicity assays.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The two screening assays detected sublethal toxins disturbing cellular energy metabolism (BSMI) as well as toxins affecting cellular proliferation (ICP) [18]. Screening of the biomass suspensions from individual colonies separated the ophiobolin-producing colonies by exhibiting a low toxic response (EC 50 < 2 µg mL −1 ) in both toxicity assays.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 29 colonies displaying unique colony morphology in daylight were screened for toxicity using two complementary rapid screening tests. The tests measured (a) the toxins affecting cellular energy metabolism, mitochondria, and ion homeostasis as the inhibition of motility of boar spermatozoa (BSMI) [18,19,27] and (b) toxins affecting macromolecular synthesis and cytostatic activity as the inhibition of proliferation of a somatic cell line, PK-15 (ICP) [16]. The toxicity tests performed with the colonies from the primary isolation plates (Figure 1) were repeated with pure, single-spore cultures.…”
Section: Experimental Designmentioning
confidence: 99%
See 2 more Smart Citations
“…expansum are able to produce chaetoglobosins and communesins, which are secreted in membrane‐surrounded vesicles and liberated as liquid exudates (Salo et al ). Recently we showed that indoor Trichoderma strains produce toxic vesicles and guttation droplets containing peptaibols (Castagnoli et al ). The reported connection between exposure to toxins and weakened immune tolerance (Genius ; Tuuminen and Lohi ), as well as our preliminary findings aroused our interest in microbial toxigenesis and vesicle formation and guttation in indoor environments.…”
Section: Introductionmentioning
confidence: 99%